OMALIZUMAB-BASED TREATMENT OF TEENAGERS, SUFFERING FROM SEVERE ATOPIC BRONCHIAL ASTHMA - T.V. Kulichenko; R.M. Torshkhoeva; L.S. Namazova (Union of pediatricians of Russia, 2008)
Omalizumab, a medicine of the recombinant humanized mono clonal antibodies to Ige, is applied in russia among teenagers throughout a year. it is prescribed to patients with severe persistent incontrolled by iks atopic bronchial asthma (BA). The article generalizes the experience of omalizumab application among teenagers and highlights the first findings in respect of its efficiency and safety. 6 month long omalizumab based treatment contributes to the reduction in the recurrence of the clinically significant BA exacerbations by 65% and the frequency of because hospitalizations by 78%. Against the background of the ongoing treatment, the indices of the bronchial passability get better; the need in the bronchial spasmolytics falls down; BA control improves. Most children have a chance to sizably reduce the dose of the inhalant glucocorticosteroids against the omalizumab based treatment. The authors pointed out to the reduced symptoms of the allergic rhinitis, grass pollen allergy, food allergy among teenagers, who have been receiving the ant Ige therapy for a long time. They also noted the satisfactory profile of omalizumab safety.Key words: omalizumab, ant Ige antibodies, bronchial asthma, treatment, children, teenagers, bronchial asthma control.